Material editorial informativo frente al acoso escolar en niños de la Escuela Isabel la Católica del cantón Píllaro - Vistin Arboleda, Santiago Joel (2024)
Bullying is a problem whose consequences are long-term and lifelong and is escalating alarmingly worldwide, this project aims to design an informative editorial material that facilitates the socialization of the subject among the students of the Isabel la Católica School as a means to fight against bullying. The application of surveys and interviews with parents and teachers has allowed the collection of the necessary information to determine the topics to be addressed in the guide. THE CLUB OF THE BRAVE is a guide that aims to empower children, becoming their companion in this daily fight against bullying, through its activities generates a bond of camaraderie and empathy among classmates thus achieving that each and every one of those present in the educational environment are part of this club and lead this fight.